Strategies for Quality Assessment of WebApps - Olsina Santos, Luis Antonio (2002)
Tutorial Goal: The aim of this tutorial consists on introducing some concepts to attribute and metric such as theory of representation, empirical and numerical domains, scale type and unit, amongst others, in order to specify a group of Web metrics useful to assess Reliability, Efficiency and Usability. In addition, manual and automatic metrics from the data collection point of view will be addressed. Ultimately, it will be analysed a set of evaluation strategies and methodologies, for different assessment purposes considering Web sites and applications (WebApps).